ANALYSIS OF FACTORS AFFECTING FISHERMAN’S INCOME IN KAMAL MUARA, NORTH JAKARTA CITY - Lola, Debie; Saparuddin; Iranto, Dicky (Transpublika Publisher, 2023)
This research aims to determine the effect of operating costs at sea, experience at sea, and length of time at sea on the income of fishermen in the Kamal Muara Village, North Jakarta. The method used in this research is a quantitative method. The reachable population in this study were all fishermen in the Kamal Muara Village Area, North Jakarta, namely a total of 200 fishermen. The 67 fisherman were randomly selected for the sampling, and a questionnaire was used to gather the data. This study use Multiple Regression Analysis as its method of analysis. The results of this study indicate that Operational costs have a positive effect of 0,515 and are significant on fishermen's income. Experience at sea has a positive and significant effect of 0,033 on fishermen's income. Likewise, there is a positive effect of 0.474 and a significant relationship between the length of time at sea and the income of fishermen, which means that each additional length of time at sea will increase the total income of fishermen by 0,474%. Simultaneously, operational costs, experience at sea, and length of time at sea has a positive and significant influence on fishermen's income.